2 mm Conventional Miniplates with Three-Dimensional Strut Plate in Mandibular Fractures - Kaushik, Shishir (Ann Maxillofac Surg, 2020)
AIM: The aim of this study was to compare 2 mm conventional miniplates with three-dimensional (3D) strut plates in the treatment of mandibular fractures treated in the Department of Oral and Maxillofacial Surgery of a college in India, during 2012–2015. MATERIALS AND METHODS: All 20 patients with mandible fracture requiring open reduction and internal fixation of the fracture were reported and reviewed in the Department of Oral and Maxillofacial Surgery of the same dental college in India, during 2012–2015. We classified the data according to the gender, age, etiology, fracture site, and method of treatment of the fractures. Fixation done in 10 patients with 2 mm conventional miniplates kept in Group I, while 10 patients with 3D strut miniplate system considered in Group II. RESULTS: Assessment of patient was done under the following parameters with follow-up at regular intervals at 2(nd) day postoperatively and at 1(st), 3(rd), and 6(th) weeks postoperatively: pain, swelling, infection, interincisal mouth opening in millimeters, paresthesia/anesthesia, mobility between fracture fragments, overall occlusion, need for any supplemental fixation, fate of implant, and complications. CONCLUSIONS: 3D titanium miniplates showed similar results when compared to standard titanium miniplates with advantages such as reduction in operative time, ease of placement, and cost-effective over the conventional plate system.